1998
DOI: 10.1002/(sici)1097-0274(199804)33:4<366::aid-ajim6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of a police cohort: 1950-1990

Abstract: This study presents findings from an updated retrospective cohort mortality study of male police officers from January 1, 1950 to December 31, 1990 (n = 2,593; 58,474 person‐years; 98% follow‐up). Significantly higher than expected mortality rates were found for all cause mortality (Standardized mortality ratio [SMR] = 110; 95% confidence interval [95% CI] = 1.04–1.17), all malignant neoplasms (SMR = 125; 95%CI = 1.10–1.41), cancer of the esophagus (SMR = 213; 95%CI = 1.01–3.91), cancer of the colon (SMR = 187… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Nearly two-fi fths (38.4%) of the officers were at high risk of having at least one of the sleep disorders: OSA, 35.1%; insomnia, 6.8%; restless legs syndrome, 0.7%; severe SWD (severe), 2.0%; and narcolepsy, 0.5% [39]. In another study of police offi cer health, all-cause mortality, particularly from malignant tumors, cirrhosis of the liver, and suicide, was signifi cantly higher in Buffalo (New York) police offi cers than in age, race, and sex-matched controls [40,41].…”
Section: Police Offi Cersmentioning
confidence: 99%
“…Nearly two-fi fths (38.4%) of the officers were at high risk of having at least one of the sleep disorders: OSA, 35.1%; insomnia, 6.8%; restless legs syndrome, 0.7%; severe SWD (severe), 2.0%; and narcolepsy, 0.5% [39]. In another study of police offi cer health, all-cause mortality, particularly from malignant tumors, cirrhosis of the liver, and suicide, was signifi cantly higher in Buffalo (New York) police offi cers than in age, race, and sex-matched controls [40,41].…”
Section: Police Offi Cersmentioning
confidence: 99%
“…Vena and colleagues ( 1986) found that Buffalo, NY, police officers had a three-fold risk of suicide compared to a control group of municipal workers ). Additionally, an updated 40-year Buffalo, NY police cohort found officers had a significantly higher risk for suicide (Standardized Mortality Ratio=156) than the general U.S. population, which includes the non-employed and institutionalized (Violanti et al 1998).…”
mentioning
confidence: 99%
“…Violanti et al's [70] cohort also documented a significantly elevated risk of dying from cirrhosis of the liver. They observed that liver disease is especially threatening to retiring officers because the mortality risk increased 3.3 times for those with over 30 years of service.…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…A 1995 study published by the Australian Bureau of Statistics found that lung cancer deaths were more common among police (7%) than the general population (5.4%). [76] Violanti et al [77] found that 40 percent of United States police officers smoke cigarettes, and they have a significantly higher mortality risk for esophageal cancer. Woolston [78] noted that death rates from esophageal cancer were two to three times higher for police officers than for the general population.…”
Section: Tobacco Usementioning
confidence: 99%
See 1 more Smart Citation